Return to play after surgical treatment for acromioclavicular joint dislocation: A systematic review - Cleary, B. P.; Hurley, E. T.; Kilkenny, C. J.; Robinson, J.; Khan, S. U.; Davey, M. S.; Anakwenze, O.; Klifto, C. S.; Mullett, H. (The American Journal of Sports Medicine, 2024)
Background: Acromioclavicular (AC) joint dislocation is a common clinical problem among young and athletic populations. Surgical management is widely used for high-grade dislocations (Rockwood III-VI) and in high-demand athletes at high risk of recurrence.